Marry your rapist! A phenomenological analysis of the experiences of women forced to marry their assaulters in their childhood - Aborisade, Richard A. (International review of victimology, 2024)
Child sexual abuse (CSA) and child marriage (CM) are two social realities that have drawn and sustained considerable research attention in Nigeria. However, research into the intersections of CSA and CM is scarce. This qualitative study explores the lived experiences of women who suffered CSA and were forced to marry their sexual assaulters in their childhood. Ten survivors were engaged in semi-structured interviews, and an interpretative phenomenological analysis (IPA) was utilized to identify four superordinate themes of participants’ experiences. These themes emphasized sexual abuse repeatedly experienced by participants, forced marriage to their assaulters, childbearing and mothering responsibilities foisted on them in their teenage, and hostilities and intimidation encountered in their marital lives. Participants provided accounts of short- and long-term physical and mental issues trailing their abuse and their coping mechanisms. The need to effectively address the cultural and religious factors that tolerate the practice of marrying CSA victims as a form of assuaging the debilitating effects of sexual assault was stressed.